2013
DOI: 10.4103/0972-124x.107469
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant therapy as monotherapy or as an adjunct to treatment of periodontal diseases

Abstract: Background:Treatment of periodontal diseases by nonsurgical debridement has been considered as a gold standard procedure. Various other treatment modalities have been tried and tested to treat periodontal diseases. The aim of this study was to investigate the effect of antioxidant therapy on the progression of periodontal disease as monotherapy and/or as an adjunct to nonsurgical debridement.Materials and Methods:70 subjects were divided into three groups, i.e. clinically healthy, gingivitis and periodontitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 6 publications
1
26
0
3
Order By: Relevance
“…Cristina Mourão et al (2015) reported that the level of LDL, glucose and uric acid increases in chronic periodontitis (40). Aditi Mathur and co-workers observed that patients suffering from periodontal disease have high level of uric acid, indicating the elevation of antioxidant function (41); our results confirm the previous findings of elevation in uric acid in periodontal disease. However, there is no evidence to report the role of dietary intervention on the serum levels of uric acid.…”
Section: Discussionsupporting
confidence: 89%
“…Cristina Mourão et al (2015) reported that the level of LDL, glucose and uric acid increases in chronic periodontitis (40). Aditi Mathur and co-workers observed that patients suffering from periodontal disease have high level of uric acid, indicating the elevation of antioxidant function (41); our results confirm the previous findings of elevation in uric acid in periodontal disease. However, there is no evidence to report the role of dietary intervention on the serum levels of uric acid.…”
Section: Discussionsupporting
confidence: 89%
“…Antioxidants play crucial role in maintaining integrity of epithelium, cell signaling and host defense mechanism [24]. Despite of limited data about use of antioxidants as adjunctive periodontal therapy; however, available studies suggest promising results to use these agents for the prevention and treatment of periodontal diseases [25,26].…”
Section: Can Other Treatment Modalities Substitute Antibiotics?mentioning
confidence: 99%
“…24 A variety of biological processes, eg., antimicrobial defense, inflammation, carcinogenesis, radiation damage, photobiological effects, and aging, involve reactive oxygen species. 25 Reactive oxygen species (ROS) play crucial roles in normal physiological processes including response to growth factors, the immune response, and apoptotic elimination of damaged cells but are also highly toxic and destructive when generated during the respiratory burst as it represents an important pathogenic mechanism for tissue damage and diseases associated with phagocytic insiltration. 26 Excessive production of ROS resulting in oxidative stress has been implicated in the pathogenesis of many human diseases including periodontitis.…”
Section: Effects Of Rosmentioning
confidence: 99%